Cognitive Aids in Medicine Assessment Tool (CMAT): preliminary validation of a novel tool for the assessment of emergency cognitive aids1. (10th March 2015) - Evans, D.; McCahon, R.; Barley, M.; Norris, A.; Khajuria, A.; Moppett, I.
Summary Applying human factors principles to the design of clinical emergency guidelines is important. The UK Civil Aviation Authority uses a Checklist Assessment Tool for evaluating the content and usability of emergency drills before introduction into service on aircraft. We hypothesised that this model could be used to develop a generic medical tool. A three‐stage modified Delphi process was used to adapt the above tool for use in designing medical emergency guidelines. The resulting Cognitive aids in Medicine Assessment Tool was then used to score and rank seven published difficult airway guidelines; the scores were used to assess its validity and reliability. Pearson's rank coefficient between these scores and scores from independent assessors was 0.89 (p = 0.007). Internal consistency, as assessed by Cronbach's alpha, was 0.74, 0.96 and 0.72 for the tool's three constituent domains of physical characteristics, content and layout/format, respectively. Inter‐rater reliability, as assessed by Cohen's kappa, ranged from 0.33 to 0.72. The adoption of our tool has the potential to improve the usability of medical emergency guidelines.